Efektivitas Yoga Kehamilan Dalam Mengurangi Rupture Perineum - Dika Yanuar Frafitasari; Alfadefi Khalifatunnisak; Ayu Rosita Dewi (Lembaga Pengembangan Kinerja Dosen, 2024)
Childbirth is a series of physiological processes that will allow some major changes in a mother to be able to give birth to her baby through the birth canal. The occurrence of perineal stiffness can actually be prepared for and anticipated, starting in early pregnancy. Preparations that can be made include doing physical exercises such as pregnant yoga. Prenatal yoga is very useful for pregnant women, especially to overcome complaints during pregnancy, reduce anxiety, improve sleep quality, and prepare physically for the labor process by training pelvic floor muscles to be stronger and more elastic so as to facilitate labor. The purpose of this study is to analyze the effect of prenatal gentle yoga on the incidence of perineal lacerations in maternity mothers in the working area of the Ngletih Health Center, Kediri Regency, in 2024. In this study, we used the quasi-experimental research method with a post-test control design. The sample used in this study was mothers who gave birth from January to April 2024, which was distinguished between the control group and the treatment group. The results of the study obtained were the influence of pregnant yoga on the incidence of perineal lacerations in maternity women, with ρ values of 0.000 < α 0.05 and significant differences in lacerations of degrees 1 and 3. From the results of this study, it can be concluded that pregnant yoga is very effective in preparing the elasticity of the perineal muscles so that it can help prevent the rupture of the delivery process.